Federal Juridiction over Labour Relations: A New Look - Scott, F.R. (Relations industrielles / Industrial Relations, 1960)
SummaryMost people in Canada have apparently come to accept the present division of legislative power between the Parliament and the legislatures as something quite natural and unchangeable. In the following article, the author originally shows that the situation has been greatly different in the past and suggests that a new look be given to the question in order that nation-wide bargaining which in fact is taking place be brought under the jurisdiction of the Parliament.